5‐Hydroxymethyl‐2′‐Deoxyuridine Residues in the Thrombin Binding Aptamer: Investigating Anticoagulant Activity by Making a Tiny Chemical Modification. Issue 16 (11th September 2014) - Virgilio, Antonella; Petraccone, Luigi; Scuotto, Maria; Vellecco, Valentina; Bucci, Mariarosaria; Mayol, Luciano; Varra, Michela; Esposito, Veronica; Galeone, Aldo
Abstract We report an investigation into analogues of the thrombin binding aptamer (TBA). Individual thymidines were replaced by the unusual residue 5‐hydroxymethyl‐2′‐deoxyuridine (hmU). This differs from the canonical thymidine by a hydroxyl group on the 5‐methyl group. NMR and CD data clearly indicate that all TBA derivatives retain the ability to fold into the "chair‐like" quadruplex structure. The presence of the hmU residue does not significantly affect the thermal stability of the modified aptamers compared to the parent, except for analogue H9, which showed a marked increase in melting temperature. Although all TBA analogues showed decreased affinities to thrombin, H3, H7, and H9 proved to have improved anticoagulant activities. Our data open up the possibility to enhance TBA biological properties, simply by introducing small chemical modifications.